SiCf / SiC ceramic-based composite material and preparation method thereof

Through SiC fiber weaving, interfacial deposition, slurry impregnation and hot press sintering, a high-density SiCf/SiC ceramic matrix composite material with high crystalline matrix was prepared, which solved the problem of difficulty in taking into account density, stoichiometric ratio and crystallinity in the prior art, and achieved excellent performance of the material in a high-temperature water-oxygen environment.

CN119638431APending Publication Date: 2025-03-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311193072.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing SiCf/SiC ceramic matrix composite preparation methods are difficult to take into account the high density, near stoichiometric ratio and high crystallinity of the matrix, which affects its application in high-temperature water-oxygen environments.

Method used

SiC fibers are used as reinforcement fibers to prepare SiCf/SiC ceramic matrix composites through SiC slurry preparation, interfacial deposition, vacuum impregnation, cut lamination and hot press sintering. The method includes chemical vapor deposition method to deposit the interface layer, vacuum impregnation of the slurry and hot press sintering.

Benefits of technology

The prepared SiCf/SiC ceramic matrix composite material has high density, near stoichiometric ratio and high crystallinity, excellent mechanical properties, high temperature resistance and oxidation resistance, and can improve service temperature and life under an oxidative environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638431A_ABST
    Figure CN119638431A_ABST
Patent Text Reader

Abstract

The invention relates to a SiCf / SiC ceramic-based composite material and a preparation method thereof. The preparation method of the SiCf / SiC ceramic-based composite material comprises the following steps: (1) weaving SiC fibers to obtain a SiC fiber woven body; (2) depositing an interface layer on the surface of the SiC fiber woven body through a chemical vapor deposition method; (3) mixing the SiC powder, a sintering aid, a dispersing agent, a binder, a plasticizer and a solvent to obtain SiC dipping slurry; (4) immersing the SiC fiber woven body on which the interface layer is deposited into the SiC dipping slurry, then taking out the completely dipped SiC woven body, and drying to obtain a SiC prepreg sheet; and (5) cutting and laminating the SiC prepreg sheets, and then carrying out hot pressed sintering to obtain the SiCf / SiC ceramic-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to SiC f / SiC ceramic matrix composite material preparation technology field, specifically relates to a method for preparing SiC based on nano slurry impregnation and hot pressing sintering f / SiC ceramic matrix composites. Background Art

[0002] Aircraft engines are known as the "heart" of aircraft vehicles. With the continuous development of aircraft engines, their thrust-to-weight ratio continues to increase. At present, the thrust-to-weight ratio of the fourth-generation aircraft engines has reached 10, and the temperature before the turbine has reached 1750°C. In the future, when the thrust-to-weight ratio of aircraft engines reaches 12-15, the average temperature before the turbine of aircraft engines will exceed 1800°C, far exceeding the temperature that traditional nickel-based high-temperature alloys can withstand. Ceramic-based composites have high temperature resistance, low density, high specific strength and specific modulus, and excellent antioxidant properties. They are a good substitute for nickel-based high-temperature alloys. Lightweight and high-strength continuous silicon carbide fiber reinforced ceramic matrix composites (SiC f / SiC) to replace traditional high-temperature alloys, which can reduce the weight of aircraft engine structures by 50-70%, increase the operating temperature by at least 200°C, and at the same time extend the service life and reduce fuel consumption.

[0003] SiC f The service environment of SiC ceramic matrix composites contains a large amount of air and water vapor generated by fuel combustion. During service, they often face the challenges of high temperature and water-oxygen oxidation. In an oxidizing environment containing water vapor, the oxidation rate of the SiC and BN interface is greatly increased, and SiC f The pores of the SiC composite material provide channels for the oxidizing gas to diffuse into the material, further accelerating the SiC f Oxidation and performance degradation of SiC / SiC composites.

[0004] At present, SiC f The preparation methods of SiC / SiC ceramic matrix composites mainly include: precursor impregnation pyrolysis (PIP), chemical vapor infiltration (CVI) and reactive melt infiltration (RMI). However, the products of the PIP method have low crystallinity and high porosity, and a large amount of carbon will remain in the matrix after the precursor is pyrolyzed. In the CVI method, the matrix needs to be deposited for dozens or even hundreds of hours, and closed pores are easily formed inside the product with high porosity. The RMI method will leave unreacted silicon inside the product. In summary, the SiC prepared by the above methods f / SiC ceramic matrix composites generally have difficulty in achieving high matrix density, near stoichiometric ratio and high crystallinity, which affects the SiC f Application of / SiC ceramic matrix composites in high temperature water and oxygen environment. Summary of the invention

[0005] In view of the above technical problems, the present invention aims to provide a highly dense, highly crystalline matrix, near stoichiometric SiC f / SiC ceramic matrix composite material and preparation method thereof. In which SiC fiber is used as reinforcing fiber, SiC is prepared through SiC slurry preparation, interface deposition, vacuum impregnation, cutting and lamination, and hot pressing sintering. f / SiC ceramic matrix composite materials.

[0006] In a first aspect, the present invention provides a SiC f A method for preparing a SiC / SiC ceramic matrix composite material, the method comprising the following steps: (1) weaving SiC fibers to obtain a SiC fiber braided body; (2) depositing an interface layer on the surface of the SiC fiber braid by chemical vapor deposition; (3) mixing SiC powder, a sintering aid, a dispersant, a binder, a plasticizer and a solvent to obtain a SiC impregnation slurry; (4) immersing the SiC fiber braided body of the deposited interface layer into the SiC impregnation slurry, and then taking out the completely impregnated SiC braided body and drying it to obtain a SiC prepreg; (5) cutting and laminating the SiC prepreg sheets, and then hot pressing and sintering them to obtain the SiC f / SiC ceramic matrix composite materials.

[0007] Preferably, the SiC fiber is woven in a 1D woven structure, a 2D woven structure, a 2.5D woven structure or a 3D woven structure.

[0008] Preferably, the chemical vapor deposition conditions are: keeping temperature at 800-1300°C for 0.5-20h, gas pressure of 1kPa-30kPa, and deposition time of 0.5-5h; The reaction gases used in the chemical vapor deposition include methane, ethane, ethylene, propylene, boron trichloride, ammonia, and methyltrichlorosilane, with a flow rate of 5 to 50 mL / min; the diluent gas and carrier gas used are hydrogen, with a flow rate of 50 to 200 mL / min.

[0009] Preferably, the interface layer on the surface of the SiC fiber includes a single-layer interface phase PyC, BN, B4C, SiC or a multi-layer interface phase (PyC-SiC). n 、(BN-SiC) n 、(BN-PyC) n ; Preferably, the thickness of the interface layer on the surface of the SiC fiber is 50 to 2000 nm.

[0010] Preferably, the sintering aid is at least one of AlN, Al2O3, Y2O3, ZrO2, MgO, SiO2, Sc2O3, and rare earth oxides; preferably, the rare earth oxide is Yb2O3; more preferably, the average powder particle size of the sintering aid is 20 to 1000 nm; The dispersant is polyvinyl pyrrolidone, polyethylene imine, tetramethyl ammonium hydroxide, fish oil or castor oil; the binder is polyvinyl butyral or polyvinyl alcohol; and the plasticizer is polyethylene glycol, dibutyl phthalate or butyl benzyl phthalate.

[0011] Preferably, the mass ratio of the SiC powder, sintering aid, dispersant, binder, plasticizer and solvent is (5-10):1:(0.2-1):(1-3):(0.5-4.2):(20-50), preferably (5-10):1:(0.2-1):(1-3):(0.5-3):(20-50).

[0012] Preferably, the SiC fiber braid is impregnated by vacuum impregnation, vibration impregnation, pressure impregnation, ultrasonic impregnation, ultrasonic-assisted vacuum impregnation, or vibration-assisted vacuum impregnation; the impregnation time is 10 min to 3 h, preferably 10 min to 2 h.

[0013] Preferably, the stacking method of SiC prepregs is to stack SiC prepregs in the same direction, stack SiC prepregs at 90° alternately, stack SiC prepregs and SiC and sintering aid mixed powder alternately, and stack SiC prepregs and SiC cast film alternately.

[0014] Preferably, the temperature of the hot pressing sintering is 1500-2000° C., the pressure of the hot pressing sintering is 5-50 MPa, and the time of the hot pressing sintering is 0.5-4 h.

[0015] In a second aspect, the present invention provides a SiC obtained according to the above preparation method. f / SiC ceramic matrix composite material, the SiC f In the SiC ceramic matrix composite material, the fiber volume fraction is 20-64% and the volume density is 2.8-3.2 g / cm 3 The open porosity does not exceed 4%, preferably does not exceed 3%, and the flexural strength is 150 to 800 MPa.

[0016] Beneficial Effects The present invention provides a SiC f The preparation method of SiC ceramic matrix composite material is to obtain SiC with high density, high thermal conductivity, high matrix crystallinity and near stoichiometric ratio through fiber weaving, interface deposition, slurry impregnation and hot pressing sintering. f / SiC composite materials. This method can adjust the fiber volume fraction in a wide range through stacking design, with a short preparation cycle. The prepared composite materials have excellent mechanical properties and high temperature resistance and oxidation resistance, which can improve the service temperature and life of the material in an oxidizing environment. It has good application prospects in high-tech fields such as hot end components of aerospace vehicles and nuclear reactors. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 2D-SiC prepared in Example 1 of the present invention f / SEM image of cross-sectional morphology of SiC ceramic matrix composites; Figure 2 2D-SiC prepared in Example 1 of the present invention f Load-displacement curve of / SiC ceramic matrix composites; Figure 3 2D-SiC prepared in Example 1 of the present invention f XRD pattern of / SiC ceramic matrix composites; Figure 4 1D-SiC prepared in Example 3 of the present invention f / SiC ceramic matrix composite material fracture morphology SEM image. DETAILED DESCRIPTION

[0018] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.

[0019] The following is an exemplary description of the SiC f A method for preparing a SiC / SiC ceramic matrix composite material. The preparation method may include the following steps.

[0020] (1) SiC fiber braiding: Continuous SiC fibers are braided to obtain a SiC fiber braid.

[0021] In some embodiments, the SiC fiber is a continuous SiC fiber with a diameter of 5-20 μm. The SiC fiber used in the present invention is a third-generation SiC fiber with an oxygen content of less than 1wt%, a carbon-silicon ratio of 0.9-1.1, and a fiber single-filament tensile strength of greater than 1.5 GPa. The main reason for selecting this type of fiber is that SiC f The preparation process of / SiC composite materials requires hot pressing and sintering at a relatively high temperature. The third-generation SiC fiber has excellent high temperature resistance and can withstand high temperatures.

[0022] In some embodiments, the SiC fibers may be woven in a 1D woven structure, a 2D woven structure, a 2.5D woven structure, or a 3D woven structure.

[0023] (2) Preparation of SiC fiber interface layer: The SiC fiber braid is placed in a tube furnace, and after the temperature is raised to the target temperature, a reaction gas, a diluent gas and a carrier gas are introduced to deposit an interface layer on the surface of the SiC fiber braid by chemical vapor deposition.

[0024] In some embodiments, the chemical vapor deposition conditions may be: keeping warm at 800-1300° C. for 0.5-20 h, gas pressure of 1 kPa-30 kPa, and deposition time of 0.5-5 h.

[0025] In some embodiments, the reaction gas used for the chemical vapor deposition may include methane, ethane, ethylene, propylene, boron trichloride, ammonia, methyltrichlorosilane depending on the deposition material; the flow rate may be 5 to 50 mL / min; the diluent gas and carrier gas used may be hydrogen, and the flow rate may be 50 to 200 mL / min.

[0026] In some embodiments, the type of SiC fiber interface layer may include a single-layer interface phase PyC, BN, B4C, SiC, or a multi-layer interface phase (PyC-SiC). n 、(BN-SiC) n 、(BN-PyC) n Preferably, the thickness of the SiC fiber interface layer can be 50-2000 nm. Controlling the thickness of the interface layer within this range can reduce the damage of the fiber and the interface during hot pressing sintering while maintaining the toughening effect of the fiber.

[0027] (3) Preparation of SiC impregnation slurry. SiC powder, sintering aid, dispersant, binder, plasticizer and solvent are mixed to obtain SiC impregnation slurry; preferably, SiC powder, sintering aid, dispersant and solvent are first mixed and ball-milled for the first time, and then binder and plasticizer are added to perform a second ball-milling to obtain SiC impregnation slurry.

[0028] Among them, the first ball milling can ensure that the nanopowder is fully dispersed. If a one-time ball milling is used to directly add dispersants, binders, etc., the binder will affect the dispersion of the powder; by adding binders and plasticizers and then performing a second ball milling, the shaping of the slurry can be better improved, so the comprehensive performance of the slurry using two ball millings is better.

[0029] In some embodiments, the average particle size of the SiC powder may be 20 to 1000 nm. A smaller powder particle size is conducive to the slurry being impregnated into the fiber bundle.

[0030] In some embodiments, the sintering aid may be at least one of AlN, Al2O3, Y2O3, ZrO2, MgO, SiO2, Sc2O3, and rare earth oxides; preferably, the rare earth oxide may be Yb2O3; more preferably, the average powder particle size of the sintering aid may be 20 to 1000 nm. The sintering aid used in the present invention can form a liquid phase to promote sintering under sintering conditions, and the sintering aid powder with a smaller particle size is conducive to the slurry impregnation into the fiber bundle.

[0031] In some embodiments, the dispersant may be polyvinyl pyrrolidone, polyethylene imine, tetramethyl ammonium hydroxide, fish oil or castor oil.

[0032] In some embodiments, the binder may be polyvinyl butyral or polyvinyl alcohol.

[0033] In some embodiments, the plasticizer may be polyethylene glycol, dibutyl phthalate, or butyl benzyl phthalate.

[0034] In some embodiments, the solvent may be deionized water, anhydrous ethanol or xylene.

[0035] In some embodiments, the mass ratio of the SiC powder, sintering aid, dispersant, binder, plasticizer and solvent can be controlled to be (5-10): 1: (0.2-1): (1-3): (0.5-4.2): (20-50), preferably (5-10): 1: (0.2-1): (1-3): (0.5-3): (20-50). By controlling the ratio of each raw material, the viscosity and solid content of the slurry can be controlled, thereby affecting the effect of the slurry impregnation process. Too high a slurry viscosity will make it difficult to immerse into the fiber bundle, and too low a slurry solid content will also affect the slurry impregnation effect.

[0036] The raw materials can be mixed by ball milling or stirring. Preferably, the ball milling method can be high-energy ball milling or planetary ball milling; the ball-to-material ratio of the ball milling can be (1-5):1, the rotation speed can be 120-400 r / min, and the ball milling time can be 6-24h; preferably, the stirring method can be mechanical stirring or magnetic stirring.

[0037] (4) Preparation of SiC prepreg: The SiC fiber braided body with the deposited interface layer is immersed in the SiC impregnation slurry, and then the completely impregnated SiC braided body is taken out and dried to obtain the SiC prepreg.

[0038] In some embodiments, the SiC fiber braid may be impregnated by vacuum impregnation, vibration impregnation, pressure impregnation, ultrasonic impregnation, ultrasonic-assisted vacuum impregnation, or vibration-assisted vacuum impregnation; the impregnation time may be 10 min to 3 h, preferably 10 min to 2 h.

[0039] Among them, the vacuum impregnation is an impregnation method in which the SiC fiber braid is immersed in the slurry and the gas inside the braid is removed by vacuum to ensure sufficient impregnation; the vibration impregnation is an impregnation method in which the SiC fiber braid is immersed in the slurry and high-frequency vibration is used to ensure sufficient impregnation; the pressure impregnation is an impregnation method in which the SiC fiber braid is immersed in the slurry and the slurry is pressed into the inside of the braid by applying pressure to ensure sufficient impregnation; the ultrasonic impregnation is an impregnation method in which the SiC fiber braid is immersed in the slurry and ultrasound is applied to ensure sufficient impregnation; the ultrasonic-assisted vacuum impregnation is an impregnation method in which the SiC fiber braid is immersed in the slurry and vacuum and ultrasound are applied at the same time; the vibration-assisted vacuum impregnation is an impregnation method in which the SiC fiber braid is immersed in the slurry and vacuum and vibration are applied at the same time.

[0040] (5) SiC f / SiC ceramic matrix composite material preparation. The SiC prepreg is cut and placed in a hot pressing mold (such as a graphite mold) for lamination, and then hot pressed and sintered to obtain the SiC f / SiC ceramic matrix composite materials.

[0041] In some embodiments, the size of the SiC prepreg after cutting can be any size that meets the requirements of the hot pressing mold (such as rectangle, circle, etc.).

[0042] In some embodiments, the stacking method of SiC prepregs can be stacking SiC prepregs in the same direction, stacking SiC prepregs at 90 degrees, stacking SiC prepregs and SiC, sintering aid mixed powders alternately, and stacking SiC prepregs and SiC cast films alternately. The stacking method can adjust the SiC f / SiC composite materials in different directions, and can control the performance of SiC f / Interlayer bonding of SiC ceramic matrix composites.

[0043] In some embodiments, the hot pressing sintering temperature may be 1500-2000°C, the hot pressing sintering pressure may be 5-50 MPa, and the hot pressing sintering time may be 0.5-4 hours. The hot pressing sintering process under appropriate conditions can achieve sintering density of the composite material while reducing damage to the fiber and interface. Too high temperature, pressure or too long time will cause damage to the fiber and interface, while too low temperature, pressure or too short time will lead to insufficient sintering density.

[0044] The preparation method provided by the present invention obtains SiC with high density, high thermal conductivity, high matrix crystallinity and near stoichiometric ratio through fiber weaving, interface deposition, slurry impregnation and hot pressing sintering. f / SiC ceramic matrix composite material. In some embodiments, the SiC provided by the present invention f In the SiC ceramic matrix composite material, the fiber volume fraction is 20-64% and the volume density is 2.8-3.2 g / cm 3 The open porosity does not exceed 4%, preferably does not exceed 3%, and the flexural strength is 150 to 800 MPa.

[0045] The preparation method provided by the present invention can adjust the fiber volume fraction in a wide range through a stacking design, and the preparation cycle is short. The prepared composite material has excellent mechanical properties and high temperature resistance and oxidation resistance, and can improve the service temperature and life of the material in an oxidizing environment. It has good application prospects in high-tech fields such as hot end components of aerospace vehicles and nuclear reactors.

[0046] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0047] Example 1

[0048] The SiC provided by the present invention f The preparation method of the SiC ceramic matrix composite material comprises the following steps: (1) SiC fiber weaving: Take 15 g of SiC fiber and weave it into a 2D plain weave SiC fiber cloth. (2) Preparation of SiC fiber interface layer. The 2D plain weave SiC fiber cloth in step (1) was placed in a tubular furnace, heated to 800°C, and then NH3, BCl3 and H2 were introduced. The gas pressure was controlled to be 3 kPa, and a BN interface layer was deposited on the surface of the SiC fiber by chemical vapor deposition. The flow rates of NH3, BCl3 and H2 were 50, 15, and 200 mL / min, respectively. The deposition time was 3 h, and the thickness of the BN interface layer was 1 μm. (3) Preparation of SiC impregnation slurry. Weigh 70.4 g SiC powder, 9.6 g sintering aid (mass ratio of Al2O3, Y2O3 and SiO2 is 9:6:5) and 4 g fish oil into a ball mill, add 286 g anhydrous ethanol as solvent into the ball mill, and then disperse by ball milling at 300 r / min for 6 h; add 20 g polyvinyl butyral ester and 40 g dibutyl phthalate into the ball milled slurry, and continue ball milling for 12 h to obtain SiC impregnation slurry. (4) Preparation of SiC prepreg. The 2D plain SiC fiber cloth with the BN interface deposited in step (2) is immersed in the impregnation slurry in step (3), and then vacuum impregnation is performed for 2 hours. The 2D plain SiC fiber cloth after vacuum impregnation is taken out and placed in an oven at 80°C for drying to obtain a SiC prepreg. (5) SiC f / SiC ceramic matrix composite material preparation. The SiC prepreg in step (4) is cut into specific sizes and stacked, placed in a hot pressing mold, and sintered at 1800°C and 15MPa for 2h to obtain 2D-SiC f / SiC ceramic matrix composite materials.

[0049] The test shows that the 2D-SiC prepared in Example 1 f The fiber volume fraction in the SiC ceramic matrix composite is 64%, and the volume density is 2.97±0.06g / cm 3 , the open porosity is 0.7±0.4%, and the flexural strength is 280.8±36.5MPa.

[0050] Figure 1 2D-SiC prepared in Example 1 of the present invention f The cross-sectional morphology SEM image of the 2D-SiC ceramic matrix composite material prepared in Example 1 of the present invention can be seen from the figure. f / SiC composite materials fibers and interfaces are intact.

[0051] Figure 2 2D-SiC prepared in Example 1 of the present invention f Load-displacement curve of 2D-SiC ceramic matrix composite material prepared in Example 1 of the present invention. f / SiC ceramic matrix composites exhibit pseudo-plastic fracture behavior.

[0052] Figure 3 2D-SiC prepared in Example 1 of the present invention f XRD pattern of the 2D-SiC ceramic matrix composite material. It can be seen from the figure that the 2D-SiC prepared in Example 1 of the present invention f / SiC ceramic matrix composite materials are basically composed of highly crystallized SiC.

[0053] Example 2

[0054] The SiC provided by the present invention f The preparation method of the SiC ceramic matrix composite material comprises the following steps: (1) SiC fiber braiding: 6 g of SiC fiber was unidirectionally wound on a graphite mold to obtain a 1D-SiC fiber braid. (2) Preparation of SiC fiber interface layer. The 1D-SiC fiber braid in step (1) was placed in a tubular furnace, heated to 800°C, and then NH3, BCl3, and H2 were introduced. The gas pressure was controlled to be 3 kPa, and a BN interface layer was deposited on the surface of the SiC fiber by chemical vapor deposition. The flow rates of NH3, BCl3, and H2 were 50, 15, and 200 mL / min, respectively. The deposition time was 1.5 h, and the thickness of the BN interface layer was 400 nm. (3) Preparation of SiC impregnation slurry. 70.4 g SiC nanopowder, 9.6 g sintering aid (mass ratio of Al2O3, Y2O3 and SiO2 is 9:6:5) and 4 g fish oil were weighed and put into a ball mill. 286 g anhydrous ethanol was added to the ball mill as solvent, and then the mixture was dispersed by ball milling at 300 r / min for 6 h. 20 g polyvinyl butyral, 5 g polyethylene glycol and 5 g dibutyl phthalate were added to the ball milled slurry, and the ball milling was continued for 12 h to obtain SiC impregnation slurry. (4) Preparation of SiC prepreg. The 1D-SiC fiber braid with the BN interface deposited in step (2) is immersed in the impregnation slurry in step (3), and then vacuum impregnation is performed for 2 hours. The 1D-SiC fiber braid after vacuum impregnation is taken out and placed in an oven at 80°C for drying to obtain a SiC prepreg. (5) SiC f / SiC ceramic matrix composite material preparation. The SiC prepreg in step (4) is cut into a specific size, alternately stacked with SiC and sintering aid mixed powder, placed in a hot pressing mold, and sintered at 1800°C and 15MPa for 2h to obtain 1D-SiC f / SiC ceramic matrix composite materials.

[0055] The test shows that the 1D-SiC prepared in Example 2 f The fiber volume fraction in the SiC ceramic matrix composite is 32%, and the volume density is 3.1±0.02g / cm 3 , the open porosity is 0.6±0.4%, and the flexural strength is 442.5±176.8MPa.

[0056] Example 3

[0057] The SiC provided by the present invention fThe preparation method of the SiC ceramic matrix composite material comprises the following steps: (1) SiC fiber braiding: 6 g of SiC fiber was unidirectionally wound on a graphite mold to obtain a 1D-SiC fiber braid. (2) Preparation of SiC fiber interface layer. The 1D-SiC fiber braid in step (1) was placed in a tubular furnace, heated to 800°C, and then NH3, BCl3, and H2 were introduced. The gas pressure was controlled to be 3 kPa, and a BN interface layer was deposited on the surface of the SiC fiber by chemical vapor deposition. The flow rates of NH3, BCl3, and H2 were 50, 15, and 200 ml / min, respectively. The deposition time was 3.5 h, and the thickness of the BN interface layer was 1 μm. (3) Preparation of SiC impregnation slurry. 70.4 g SiC nanopowder, 9.6 g sintering aid (mass ratio of Al2O3, Y2O3 and SiO2 is 9:6:5) and 4 g fish oil were weighed and put into a ball mill. 286 g anhydrous ethanol was added to the ball mill as solvent, and then the mixture was dispersed by ball milling at 300 r / min for 6 h. 20 g polyvinyl butyral, 5 g polyethylene glycol and 5 g dibutyl phthalate were added to the ball milled slurry, and the ball milling was continued for 12 h to obtain SiC impregnation slurry. (4) Preparation of SiC prepreg. The 1D-SiC fiber braid with the BN interface deposited in step (2) is immersed in the impregnation slurry in step (3), and then vacuum impregnation is performed for 2 hours. The 1D-SiC fiber braid after vacuum impregnation is taken out and placed in an oven at 80°C for drying to obtain a SiC prepreg. (5) SiC f / SiC ceramic matrix composite material preparation. The SiC prepreg in step (4) is cut into a specific size, alternately stacked with SiC and sintering aid mixed powder, placed in a hot pressing mold, and sintered at 1800°C and 15MPa for 2h to obtain 1D-SiC f / SiC ceramic matrix composite materials.

[0058] The test shows that the 1D-SiC prepared in Example 3 f The fiber volume fraction in the SiC ceramic matrix composite is 34%, and the volume density is 2.92±0.01g / cm 3 , the open porosity is 3.6±0.4%, and the flexural strength is 226.5±29.3MPa.

[0059] Figure 4 1D-SiC prepared in Example 3 of the present invention f The fracture morphology SEM image of the 1D-SiC ceramic matrix composite material prepared in Example 3 of the present invention can be seen from the figure. f / SiC ceramic matrix composites show obvious fiber pull-out phenomenon when they fracture.

[0060] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A SiC f A method for preparing a SiC / SiC ceramic matrix composite material, characterized in that: The preparation method comprises the following steps: (1) weaving SiC fibers to obtain a SiC fiber braided body; (2) depositing an interface layer on the surface of the SiC fiber braid by chemical vapor deposition; (3) mixing SiC powder, a sintering aid, a dispersant, a binder, a plasticizer and a solvent to obtain a SiC impregnation slurry; (4) immersing the SiC fiber braided body of the deposited interface layer into the SiC impregnation slurry, and then taking out the completely impregnated SiC braided body and drying it to obtain a SiC prepreg; (5) cutting and laminating the SiC prepreg sheets, and then hot pressing and sintering them to obtain the SiC f / SiC ceramic matrix composite materials.

2. The preparation method according to claim 1, characterized in that: The SiC fiber is woven in a 1D woven structure, a 2D woven structure, a 2.5D woven structure or a 3D woven structure.

3. The preparation method according to claim 1 or 2, characterized in that: The chemical vapor deposition conditions are: keeping temperature at 800-1300° C. for 0.5-20 h, gas pressure of 1 kPa-30 kPa, and deposition time of 0.5-5 h; The reaction gases used in the chemical vapor deposition include methane, ethane, ethylene, propylene, boron trichloride, ammonia, and methyltrichlorosilane, with a flow rate of 5 to 50 mL / min; the diluent gas and carrier gas used are hydrogen, with a flow rate of 50 to 200 mL / min.

4. The preparation method according to any one of claims 1 to 3, characterized in that The types of interface layers on the surface of SiC fibers include single-layer interface phase PyC, BN, B4C, SiC or multi-layer interface phase (PyC-SiC) n 、(BN-SiC) n 、(BN-PyC) n ; Preferably, the thickness of the interface layer on the surface of the SiC fiber is 50 to 2000 nm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The sintering aid is at least one of AlN, Al2O3, Y2O3, ZrO2, MgO, SiO2, Sc2O3, and rare earth oxides; preferably, the rare earth oxide is Yb2O3; more preferably, the average powder particle size of the sintering aid is 20 to 1000 nm; The dispersant is polyvinyl pyrrolidone, polyethylene imine, tetramethyl ammonium hydroxide, fish oil or castor oil; the binder is polyvinyl butyral or polyvinyl alcohol; and the plasticizer is polyethylene glycol, dibutyl phthalate or butyl benzyl phthalate.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the SiC powder, sintering aid, dispersant, binder, plasticizer and solvent is (5-10):1:(0.2-1):(1-3):(0.5-4.2):(20-50), preferably (5-10):1:(0.2-1):(1-3):(0.5-3):(20-50).

7. The preparation method according to any one of claims 1 to 6, characterized in that The impregnation method of the SiC fiber braid is vacuum impregnation, vibration impregnation, pressure impregnation, ultrasonic impregnation, ultrasonic-assisted vacuum impregnation, and vibration-assisted vacuum impregnation; the impregnation time is 10 minutes to 3 hours, preferably 10 minutes to 2 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The stacking methods of SiC prepregs are as follows: stacking SiC prepregs in the same direction, stacking SiC prepregs at 90° alternately, stacking SiC prepregs and SiC and sintering aid mixed powder alternately, and stacking SiC prepregs and SiC cast film alternately.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The temperature of the hot pressing sintering is 1500-2000° C., the pressure of the hot pressing sintering is 5-50 MPa, and the time of the hot pressing sintering is 0.5-4 hours.

10. A SiC prepared by the preparation method according to any one of claims 1 to 9 f / SiC ceramic matrix composite material, characterized in that The SiC f / SiC ceramic matrix composites, the fiber volume fraction is 20-64%, and the volume density is 2.8-3.2 g / cm 3 , the open porosity does not exceed 4%, preferably does not exceed 3%, and the flexural strength is 150 to 800 MPa.

Citation Information

Patent Citations

  • Method for preparing thermal structure composite material through hot pressing method

    CN106966745A

  • Multi-layer interface coating, preparation method and ceramic matrix composite material preparation method

    CN114105662A

  • Method for preparing monocrystalline silicon carbide nanofiber / silicon carbide ceramic-based composite material through nano-impregnation transient eutectic

    CN114751760A

  • Method for manufacturing high density sicf / sic composites

    KR1020100123048A